Season and Discharge Predict Downstream Emigration Rates for Reservoir Sport Fish Populations. (1st November 2021) - Shane, Keith D.; Page, Kevin S.; Pritt, Jeremy J.; Conroy, Joseph D.; Marschall, Elizabeth A.
Abstract: Given the importance of reservoir fisheries and the investments made by fisheries management agencies to create and maintain these fisheries, the loss of reservoir‐stocked fish through downstream emigration warrants action to be taken to understand and prevent it. The factors driving emigration of reservoir fish and the measurable effects of emigration on fish population dynamics are not well understood. In this study, we sought to understand the seasonal emigration patterns of two popular sport fish, saugeye (female Walleye Sander vitreus × male Sauger Sander canadensis ) and Muskellunge Esox masquinongy, and determine if their annual declines in abundance were correlated with predicted annual emigration rates. We modeled daily emigration probabilities of saugeye and Muskellunge from PIT tag data collected in the dam spillway of an Ohio reservoir. Using data on discharge from previous years, these models were used to estimate annual emigration rates, which were regressed against historical catch data to test whether emigration explained annual cohort declines. Our models showed that downstream emigration from the reservoir occurred primarily during spring for both species, especially during periods of high reservoir discharge. All saugeye and nearly all Muskellunge emigrants were adults, with 13% of tagged adult saugeye and 17% of tagged adult Muskellunge emigrating. Our models predicted historical annual emigration losses (across all age‐classes) as high as 24% for saugeye and 8.6% for Muskellunge. Furthermore, historical annual emigration rates were negatively related to catch rates for both species. These results illustrate that, depending on flow regime and seasonal effects on fish movements, emigration can have measurable effects on reservoir sport fish populations. As such, it is important to understand the factors driving downstream migration and use this understanding to inform decisions on potential mitigation of emigration as well as fish stocking decisions.